Assessment and evaluation of Chitosan‐Metamizole nanoparticles for the fracture healing and analgesic effect: Preclinical study in rat model - Li Yin; Liyong Yuan; Chunling Peng; Qionghua Wang (IET Nanobiotechnology)
Abstract To assess and evaluate Chitosan‐Metamizole nanoparticles for fracture healing and analgesic potential, nanoparticles were formulated using the ionotropic gelation method. The nanoparticles were evaluated for particle size, zeta potential, polydispersity index, loading efficiency, surface characteristics and drug release properties. The analgesic activity was determined in carrageenan‐induced arthritic male Wister rats. Further fracture healing potency, mechanical testing, radiographic examination and bone histology of the femur were studied. The drug loading efficiency of 11.38%–17.45%, particle size of 140–220 nm, and zeta potential of 19.12–23.14 mV were observed with a spherical, smooth appearance. Nanoparticles showed sustained release behaviour over a longer period. Nearly 4‐fold inhibition of oedema was observed in animals treated with nanoparticles with excellent fracture healing potential. The femurs treated with nanoparticles required greater force to fracture. Nanoparticles significantly improved the strength and healing process. Histopathological studies showed the potential of nanoparticles in the healing process. The study confirmed the potential of nanoparticles in fracture healing and enhancement of analgesic activity.